Analysis of Dix-Hallpike maneuver induced nystagmus based on virtual simulation. (4th May 2021) - Zheng, Yanyan; Wu, Shuzhi; Yang, Xiaokai
Abstract: Background: How to interpret the various forms of nystagmus induced by the Dix-Hallpike maneuver has been the hotspot and difficulty of research. Objectives: Analysis of the types of nystagmus induced by Dix-Hallpike maneuver, and establish a diagnosis strategy based on dynamic nystagmus observation. Materials and methods: We observed the otolithic movements at different locations during the Dix-Hallpike maneuver through physical virtual simulation experiments and inferred the nystagmus performance, so as to establish the nystagmus interpretation rules for the repeated Dix-Hallpike maneuver. Results: There are six types of nystagmus induced by the Dix-Hallpike maneuver. Nystagmus induced by the unilateral Dix-Hallpike maneuver does not accurately locate the otolith. The typical nystagmus that is consistent before and after the repetition of the Dix-Hallpike maneuver is the outward and upbeat nystagmus, considering the ipsilateral posterior semicircular canal BPPV. Conclusion: The atypical nystagmus often turns negative when the Dix-Hallpike maneuver is repeated. If the repeat test is positive and consistent with the results of the first diagnostic test, the otolith can be accurately located.